Synthetic and mechanistic studies of novel dioxiranes - Frohn, Michael John, author; Shi, Yian, advisor (Colorado State University. Libraries, 2000)
Epoxides are versatile synthetic intermediates. The epoxidation of olefins via dioxiranes provides a particularly efficient route towards their synthesis, and studies into an asymmetric version have received great interest recently. Our group has been active in this area, and we have found an efficient asymmetric epoxidation method for simple unfunctionalized olefins using a fructose-derived ketone as catalyst and Oxone as oxidant. The asymmetric monoepoxidation of unsymmetrical conjugated dienes has been studied using the fructose-derived ketone. The regio- and enantioselectivities have been found to be very high in most cases. As a result, a variety of synthetically useful vinyl epoxides can be readily produced in optically enriched form. The method is complementary to the selective epoxidation of conjugated dienes catalyzed by chiral (salen)Mn complexes, in which the c/j-olefins are preferentially epoxidized. It is also complementary to the Sharpless asymmetric epoxidation of dienyl alcohols, which gives complete regioselective epoxidation at the epoxide proximal to the alcohol. The kinetic resolution of racemic olefins using this asymmetric epoxidation strategy has also been studied intensively. Very high levels of resolution efficiency have been observed with both 1,6- and 1,3-disubstituted cyclohexenes. Exocyclic cyclohexenes and acyclic olefins are resolved less efficiently. The method can be viewed as a valuable alternative to some of the existing kinetic resolutions since it does not involve transition metals and the experimental procedure is simple. Finally, in conjunction with these asymmetric studies, the efficient racemic epoxidation of olefins using dimethyldioxirane at high pH has also been discovered. Nearly every class of olefins can be efficiently epoxidized using the general procedure that has been developed. In addition, it is highly practical, as epoxidations of 0.1 mol can be undertaken without complications. Further advantages include a simple workup procedure and the use of environmentally benign ingredients.
Page 51 missing in number only.
Keywords: organic chemistry